Impact of probiotics and prebiotics targeting metabolic syndrome. (January 2020) - Xavier-Santos, Douglas; Bedani, Raquel; Lima, Egidio Dorea; Saad, Susana Marta Isay
Graphical abstract: Highlights: The effects of pro- and prebiotic intake on metabolic syndrome (MetS) was reviewed. MetS results from interactions between innate immune system and the gut microbiota. Pro- and prebiotics have specifics functions in the intestinal microbiota modulation. Intestinal microbiota modulation contributes for the prevention of MetS components. Abstract: Several studies are contributing to the better understanding of the impact of probiotics and prebiotics on the modulation of the intestinal microbiota and subsequent effects on the host's health. This review aimed to discuss the results of studies using different experimental models to evaluate the impact of the supplementation with probiotics and/or prebiotics on the different risk factors related to metabolic syndrome (MetS). A better understanding of the daily supplementation of probiotics and prebiotics regarding the mechanisms involved in the modulation of the intestinal microbiota and the immune system of patients suffering from this metabolic disorder is necessary to establish the efficiency of possible biomarkers that could contribute towards a health claim. Although the results might be promising, the functionality of probiotics and prebiotics on the intestinal microbiota and its relationship with MetS are still poorly understood to indicate their consumption for prevention and management of MetS in clinical practice.